Tobacco Through Time (Bloomsbury Publishing (UK), 2026)
Throughout human history there are arguably few plants that have had such a significant impact on the lives of people as tobacco. Yet, despite its unparalleled dissemination across human societies, histories of the plant, its use and impact have been dominated by Western European experiences, and based upon a relatively narrow span of sources and records. This open access collection readdresses this imbalance, showcasing a range of interdisciplinary approaches to decentre unilinear, Western and economically-focused accounts of tobacco. From archaeological analysis of bone and dental records, to anthropological considerations of material culture and historical investigations into tobacco’s role in the expansion of colonial power and the slave trade, this book employs a range of methods and sources to broaden our understanding of the impact of tobacco on health, population, genetics, consumption, economics, trade, gender and ethnicity. With case studies in North Africa, India and Sri Lanka alongside the Americas and Europe, it seeks to broaden perspectives on the use of tobacco beyond the West, and combine disciplinary methods to better assess its enduring impact on our species. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by UKRI.